Epitope mapping reveals the binding mechanism of a functional antibody cross-reactive to both human and murine programmed death 1. Issue 4 (19th May 2017) - Li, Dong; Xu, Jianqing; Wang, Zhuozhi; Gong, Zhen; Liu, Jieying; Zheng, Yong; Li, Jian; Li, Jing
ABSTRACT: Of the inhibitory checkpoints in the immune system, programmed death 1 (PD-1) is one of the most promising targets for cancer immunotherapy. The anti-PD-1 antibodies currently approved for clinical use or under development bind to human PD-1 (hPD-1), but not murine PD-1. To facilitate studies in murine models, we developed a functional antibody against both human and murine PD-1, and compared the epitopes of such antibody to a counterpart that only bound to hPD-1. To quickly identify the epitopes of the 2 antibodies, we used alanine scanning and mammalian cell expression cassette. The epitope identification was based on PD-1-binding ELISA and supported by affinity ranking of surface plasmon resonance results. The hPD-1 epitopes of the 2 functional antibodies were also compared with the binding region on hPD-1 that is responsible for PD-L1 interaction. In silico modeling were conducted to explain the different binding modes of the 2 antibodies, suggesting a potential mechanism of the antibody cross-species binding.